Chestnut street ebook - Binchy, Maeve (2014)
A New York Times Bestseller   From the author of  A Week in Winter  and  Minding Frankie : a poignant and heartwarming collection of stories centered on the comings and goings of one delightful street in Dublin   “Packed with charming takes on people's quirks and foibles, nosy neighbors and friendly ones. Binchy eloquently exposes and explores relationships between parents and children, husbands and wives, longtime and recently acquired friends.”— The Boston Globe   Imagined with the humor and understanding that are hallmarks of Maeve Binchy’s storytelling, the world of Chestnut Street captivates us with its joys and sorrows.   Maguire, the window cleaner, must do more than he bargained for in order to protect his son. Nessa Byrne’s aunt visits from America every summer, turning Nessa’s house—and world—upside down. Lilian, a generous girl with a big heart, has a fiancé whom no one approves of. Melly’s gossipy ways help Madame Magic, a self-styled fortune-teller, get everyone on the right track. And Dolly, an awkward young girl, discovers more about her perfect mother than she ever wanted to know.